RELATIONSHIP BETWEEN ULTRASONOGRAPHIC CRITERIA, CLINICAL MANIFESTATIONS AND LIFE QUALITY PARAMETERS IN PATIENTS WITH LOWER EXTREMITY VARICOSE VEIN DISEASE - Atamaniuk, O.Yu.; Skrypko, V.D.; Atamaniuk, V.M.; Bybliuk, Yu.Y. (World of Medicine and Biology, 2022)
Comparing the efficacy of modern methods of treatment of the varicose veins disease of the lower extremities requires accurate documentation of the clinical, anatomical and functional situation in each patient using standardized and proven methods. In our study we analyzed the relationship between the diameter of the great saphenous vein determined at the level of the saphenous-femoral joint, for 3 cm distal and in the middle of the thigh, with the duration of reflux. We also studied the severity of clinical manifestations according to CEAP classification, VCSS varicose disease severity scale and quality of life with the help of the AVVQ questionnaire. According to the results of the study, it the importance of determining the diameter and reflux of the great saphenous vein at the level of saphenous-femoral joint, as there is a statistically significant difference in the mean level of correlation between these indicators and survey areas provided by consensus documents. It has been found that with increasing vein diameter, a more severe clinical class and manifestations of the disease are diagnosed. The relationship between the severity of varicose veins of the lower extremities on the VCSS scale and the assessment of the quality of life using the AVVQ questionnaire was established.
Keywords: varicose vein disease; vein diameter; severity; quality of life